Assessment of conditions for the formation and distribution of traps and deposits in the Caspian region - U. S. Serikova; P. A. Romanov (Известия высших учебных заведений: Геология и разведка)
Introduction. The conditions of formation and distribution of accumulations of traps and deposits in the Caspian region are considered.Goal. Assessment of conditions for the formation and distribution of traps and deposits in the Caspian region.Materials and methods. Statistical generalization and systematization of data and materials partially borrowed from reference literature, stock sources, field data and published works [2, 5, 7].Results. As a result, mainly in platform shelf conditions and in local areas of relative stabilization or weak oscillatory movements, the formation of lithological-stratigraphic and combined traps can be associated with a variety of accumulative and erosive-accumulative forms of coastal and isolated shallow waters remote from the coast. Finally, separate groups of traps are formed during periods of relative geodynamic stabilization, in water areas where conditions for carbonation accumulation and the formation of biogenic structures are provided.